Influence of Zn2+ on Corrosion Behavior of Ti in H2SO4 Solution with F− - Xinxin LIU; Yoganandan GOVINDARAJ; Masatoshi SAKAIRI (Electrochemistry)
The influence of Zn2+ on the corrosion behavior of Ti in 1.68 mol L−1 H2SO4 with 0.058 mol L−1 F− solutions was investigated by mass loss measurements, electrochemical tests, and surface observation and analysis. Different concentrations of Zn2+ (0.0002 mol L−1, 0.002 mol L−1, 0.02 mol L−1, 0.2 mol L−1) were added to the solutions to investigate the effect of Zn2+ concentration. The mass loss results showed that the presence of Zn2+ in the corrosive solution could accelerate the corrosion of Ti. From the electrochemical tests results, the corrosion resistance is decreased while increasing the Zn2+ concentration. An adsorption-desorption model of TiFx3−x on Ti was proposed: Zn2+ could inhibit the adsorption process of TiFx3−x and reduce the surface coverage of TiFx3−x, which could provide more active site for Ti to dissolve, resulted in the severe corrosion of Ti.